Implementing Additive Manufacturing for Spare Parts in the Automotive Industry - A case study of the use of additive manufacturing for spare parts - Robert, Augustsson; Denijel, Becevic (My University, 2015)
Previous research investigates what causes problems in the supply chain. However, there is a gap in research for possible solutions to these problems. As logistic systems grow bigger they become more difficult to manage and therefore it’s vital to find resources to minimize risk and increase efficiency. Research suggests that additive manufacturing could be a solution to some of the problems that the supply chain may face. The paper aims to investigate if inventory costs for low turnover spare parts can be lowered, but still offer the same availability by using additive manufacturing. Therefore, the nature of this research was to investigate the consequences of implementing additive manufacturing for manufacturing spare parts in the automotive industry. A case study was done with the cooperation with a big truck manufacturer, which had done similar research and wanted to take necessary steps to increase the management capacity. In order to measure the effect that additive manufacturing would have on the supply chain, spare parts that could possibly be manufactured using additive manufacturing and be profitable were identified. Different methods that was suggested by literature was used in order to find a sample; the first method was a hierarch process and the second method used three factors Annual Usage, Standard Cost of Sales and Lead time. The framework for finding the best-suited spare parts for additive manufacturing could be applied again in different divisions of the supply chain. The identified spare parts would only be theoretically beneficial to produce with additive manufacturing. To get real measurements, the identified spare parts were subjected to a cost analysis. Two different comparisons was done; the first was done by using a mathematical model from a previous case study and the second was done by cost estimations from third party additive manufacturers. The data from these sources was compared with the actual cost gathered from the truck manufacturers master system. From the empiric findings showed that 6.7% - 20% of a sample of 30 products was profitable compared to the actual cost. Investigating transportation this increased to 6.7% - 23.3%. However, the main finding was the lowering of spare parts lead-time. Of the profitable spare parts 66.6% - 85.7% could lower the lead-time down to 1-2 weeks. If investigating the whole sample of 30 products the lead-time could be lowered for 19 products (63.3%). This could implicate that the main benefit of using additive manufacturing is a big increase in customer service. Arguably, if the technology for additive manufacturing develops in the same rate as in the past, it would be worthwhile to do further investigation in this area as cost could go down.
Keywords: Transport; Övrig industriell teknik och ekonomi; Transport; Other industrial engineering and economics